URGENSI KURSUS PRA NIKAH DALAM MEMBENTUK KELUARGA DI ERA MODERN - Mughni Labib Ilhamuddin Is Ashidiqie (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2020)
This article elaborates the urgency of pre-marital courses as an effort to build a family in the modern era. The very reason is that, at present, family is one of the keys to achieving national development success. In assessing the urgency of the pre-marital course, the researcher used a normative juridical approach by tracing the rules regarding pre-marital course and family development, as well as other literature related to the topic under discussion. This research was analytical descriptive, aiming to describe and analyze the overall object under research. the research result indicates that families in the modern era play a very important role to achieve national development success as one of the issues in national development is family. Therefore, building a prosperous family life is a necessity. One of the efforts to achieve said objective is by holding pre-marital courses. Moreover, judging from the subjects in pre-marital courses, pre-marital courses have a relevance to national development through building resilient families. However, the researcher found that there was a subject that had not been explicitly stated in the courses, namely gender partnerships. Therefore, it is needed to add to the courses as in the context of building resilient families, one of the variables is gender partnership.